Hepatitis E virus seroepidemiology: a post-earthquake study among blood donors in Nepal. Issue 1 (December 2016) - Shrestha, Ashish; Flower, Robert; Seed, Clive; Rajkarnikar, Manita; Shrestha, Shrawan; Thapa, Uru; Hoad, Veronica; Faddy, Helen
Abstract Background As one of the causative agents of viral hepatitis, hepatitis E virus (HEV) has gained public health attention globally. HEV epidemics occur in developing countries, associated with faecal contamination of water and poor sanitation. In industrialised nations, HEV infections are associated with travel to countries endemic for HEV, however, autochthonous infections, mainly through zoonotic transmission, are increasingly being reported. HEV can also be transmitted by blood transfusion. Nepal has experienced a number of HEV outbreaks, and recent earthquakes resulted in predictions raising the risk of an HEV outbreak to very high. This study aimed to measure HEV exposure in Nepalese blood donors after large earthquakes. Methods Samples (n = 1, 845) were collected from blood donors from Kathmandu, Chitwan, Bhaktapur and Kavre. Demographic details, including age and sex along with possible risk factors associated with HEV exposure were collected via a study-specific questionnaire. Samples were tested for HEV IgM, IgG and antigen. The proportion of donors positive for HEV IgM or IgG was calculated overall, and for each of the variables studied. Chi square and regression analyses were performed to identify factors associated with HEV exposure. Results Of the donors residing in earthquake affected regions (Kathmandu, Bhaktapur and Kavre), 3.2% (54/1, 686; 95% CI 2.7–4.0%) were HEV IgM positive and two donors were positive for HEV antigen. Overall, 41.9% (773/1, 845; 95% CI 39.7–44.2%) of donors were HEV IgG positive, with regional variation observed. Higher HEV IgG and IgM prevalence was observed in donors who reported eating pork, likely an indicator of zoonotic transmission. Previous exposure to HEV in Nepalese blood donors is relatively high. Conclusion Detection of recent markers of HEV infection in healthy donors suggests recent asymptomatic HEV infection and therefore transfusion-transmission in vulnerable patients is a risk in Nepal. Surprisingly, this study did not provide evidence of a large HEV outbreak following the devastating earthquakes in 2015.